High risk of unexpected late fetal death in monochorionic twins despite intensive ultrasound surveillance: a cohort study. - Olivia Barigye; Lucia Pasquini; Paula Galea; Helen Chambers; Lucy Chappell; Nicholas M Fisk (PLoS Medicine, 2005)
BACKGROUND: The rationale for fetal surveillance in monochorionic twin pregnancies is timely intervention to prevent the increased fetal/perinatal morbidity and mortality attributed to twin-twin transfusion syndrome and intrauterine growth restriction. We investigated the residual risk of fetal death after viability in otherwise uncomplicated monochorionic diamniotic twin pregnancies. METHODS AND FINDINGS: We searched an electronic database of 480 completed monochorionic pregnancies that underwent fortnightly ultrasound surveillance in our tertiary referral fetal medicine service between 1992 and 2004. After excluding pregnancies with twin-twin transfusion syndrome, growth restriction, structural abnormalities, or twin reversed arterial perfusion sequence, and monoamniotic and high-order multiple pregnancies, we identified 151 uncomplicated monochorionic diamniotic twin pregnancies with normal growth, normal liquor volume, and normal Doppler studies on fortnightly ultrasound scans. Ten unexpected intrauterine deaths occurred in seven (4.6%) of 151 previously uncomplicated monochorionic diamniotic pregnancies, within 2 wk of a normal scan, at a median gestational age of 34(+1) wk (weeks(+days); range 28(+0) to 36(+3)). Two of the five cases that underwent autopsy had features suggestive of acute late onset twin-twin transfusion syndrome, but no antenatal indicators of transfusional imbalance or growth restriction, either empirically or in a 1:3 gestation-matched case-control comparison. The prospective risk of unexpected antepartum stillbirth after 32 wk was 1/23 monochorionic diamniotic pregnancies (95% confidence interval 1/11 to 1/63). CONCLUSION: Despite intensive fetal surveillance, structurally normal monochorionic diamniotic twin pregnancies without TTTS or IUGR are complicated by a high rate of unexpected intrauterine death. This prospective risk of fetal death in otherwise uncomplicated monochorionic diamniotic pregnancies after 32 wk of gestation might be obviated by a policy of elective preterm delivery, which now warrants evaluation.